Report of Beta Thalassemia in Newar Ethinicity - Bhatt, Rajendra Dev (Annals of Clinical Chemistry and Laboratory Medicine, 2018)
Beta thalassemia trait is a heterogeneous autosomal recessive form of beta thalassemia. Individual with beta thalassemia are clinically asymptomatic. Here we have described a case that has been incidentally diagnosed as beta thalassemia trait. A 31 year old male form Newar Community came to hospital for routine health checkup was send for hematological investigation. On examination, his red cell morphology was found to be microcytic hypochromic and his hemoglobin concentration was mildly decrease. His other parameters was evaluated and requested for analysis of iron profile and hemoglobin electrophoresis. Iron profile test was normal. Hemoglobin electrophoresis showed prominent band in HbA2 region. Presence of HbA2 band was confirmed by hemoglobin variant HPLC analysis. A diagnosis of heterozygous beta thalassemia trait was made. Prevalence of beta thalassemia gene in Tharu population was reported but its presence in other communities is still unknown so it is recommended to study the prevalence of beta thalassemia gene in Newar community as well.